#TITLE_ALTERNATIVE# - (NIM 10102028), ANDRIANSYAH
This paper presents a new methodology to simulate a pursuit-evasion model. With working on this simulation, we want to approach an agent-based behavior through multi-player pursuit and evasion model. The proposed model is derived precisely by observing the nature phenomenon and presented on a differential equation system. This model is called Hunter-Prey Model. The corresponding model offers a simple form of pursuit-evasion model that can be implemented on real-time systems for autonomous vehicles. We also explore different values of speed which lead to different performance for some players. We illustrate our approach on a three player Hunter-Prey Simulation and present simulation results.